2018
DOI: 10.1111/ijd.13884
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity of subclassifying warfarin‐associated nonuremic calciphylaxis: a retrospective cohort study

Abstract: Though this study is limited by its retrospective nature and the relatively small number of patients studied, available data do not support subclassifying patients with nonuremic calciphylaxis as having warfarin-associated or warfarin-unassociated disease. Rather, the body of literature would suggest that identification and correction of underlying disorders of hypercoagulability should be prioritized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Patients with diabetes mellitus and cancer had a preference for calciphylaxis. Warfarin, as an anticoagulant commonly used in clinic, is a well-recognized potential precipitating factor of calciphylaxis (17,18). In this epidemiological investigation, there was found that it memorably increased the risk of calciphylaxis although only 8.33% of patients had a history of warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes mellitus and cancer had a preference for calciphylaxis. Warfarin, as an anticoagulant commonly used in clinic, is a well-recognized potential precipitating factor of calciphylaxis (17,18). In this epidemiological investigation, there was found that it memorably increased the risk of calciphylaxis although only 8.33% of patients had a history of warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin-associated calciphylaxis is a crucial clinical subgroup with independent pathophysiologic features [45]. Warfarin can not only promote vascular calcification by inhibiting the vitamin K-dependent matrix Gla protein which prevents calcium deposition in arteries, but also directly increase thrombosis through the coagulation pathway [45,46]. And the latest research observed that the ESKD undergoing hemodialysis is a deficiency state of vitamin K [47].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies have revealed that ESRD patients with mechanical valves more commonly present with bleeding or thromboembolic events than structural deterioration of bioprosthetic valves (17,24,27). Patients with ESRD receiving mechanical valve replacement require warfarin for stroke prevention, which is usually associated with a higher risk of bleeding event, metastatic calcification, and catastrophic calciphylaxis (15,16). The aforementioned complications could increase the periprocedural mortality, as shown in the present findings.…”
Section: Long-term Outcome Of Mechanical and Bioprosthetic Valve Replacement Among Esrd Patientsmentioning
confidence: 49%
“…In contrast, patients with ESRD receiving anticoagulants are at higher risk of bleeding, (13,14) metastatic calcification, and even calciphylaxis (15,16). In addition, ESRD patients have a short life expectancy.…”
Section: Introductionmentioning
confidence: 99%